2006
DOI: 10.1109/iccd.2006.4380855
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Dynamic Thermal Management: A Markovian Decision-based Approach

Abstract: -This paper proposes a stochastic dynamic thermal management (DTM) technique in high-performance VLSI system with especial attention to the uncertainty in temperature observation. More specifically, we propose a stochastic thermal management framework to improve the accuracy of decision making in DTM, which performs dynamic voltage and frequency scaling to minimize total power dissipation and onchip temperature. A key characteristic of the framework is that thermal states are controlled by stochastic processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Several new controller designs have been proposed in the recent years for multicore DEM [Bartolini et al 2011;Jung and Pedram 2006;Wang et al 2009;Zanini et al 2009]. These controllers can be broadly classified based on their approaches, viz.…”
Section: Overview Of Proposed Steam Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…Several new controller designs have been proposed in the recent years for multicore DEM [Bartolini et al 2011;Jung and Pedram 2006;Wang et al 2009;Zanini et al 2009]. These controllers can be broadly classified based on their approaches, viz.…”
Section: Overview Of Proposed Steam Controllermentioning
confidence: 99%
“…statistical and control-theoretic. Jung and Pedram [2006] propose a statistical technique based on partially observable Markov chains to predict an optimal processor frequency setting. While their approach avoids the need for learning of the processor power or thermal models, their algorithm requires complex computations, and the number of DVFS state searches grow exponentially with the number of processor cores.…”
Section: Overview Of Proposed Steam Controllermentioning
confidence: 99%
“…The temperature of core is modeled with linear regression and found that it is linear function of frequency and workload in [10] and after modeling the regression variables are reduced by principal component analysis. The stochastic nature of temperature variation by modeling and accessing the uncertainty in core temperature is constructed in [11]. Using Markov decision process the thermal state was modeled to determine the next state and DVFS was used for thermal control.…”
Section: A Single Corementioning
confidence: 99%
“…0, for , (17) where , denotes the probability that the system will next come to state if it is currently in state and action is chosen. Constraints (15) -(17) capture the properties of a CTMDP.…”
Section: The Local Agentsmentioning
confidence: 99%
“…Each core in the server cluster is modeled using a continuous-time Markov decision process (CTMDP) [17] [18], in which actions are execution frequencies (and supply voltages) for processing the service requests. We know that a higher execution frequency will result in a shorter response time, but a significant increase in power consumption [12][13] [14].…”
Section: Introductionmentioning
confidence: 99%